ACHIEVING DECENT WORK FOR DIGITAL PLATFORM WORKERS IN SOUTH AFRICA - William Manga Mokofe (Obiter, 2022)
Across the globe, digital platform workers lack access to basic workplace rights and protections. Lacking the ability to bargain collectively as a result of this novel, digitally managed market for work, many platform workers have jobs characterised by long and irregular hours, lack of representation, low remuneration, high stress levels, and little ability to negotiate wages or working conditions with their employers. This article questions the narrow definition of “employee” that limits the protection afforded to these workers. Workers have been largely incorrectly classified as independent contractors rather than as employees, a classification that has been challenged in courts around the world. This article explores possible strategies and offers suggestions to improve this situation to achieve decent work for such workers. The article concludes by suggesting that the solution to challenges associated with platform workers rests, among others, in social dialogue, legal solutions, new union strategies, and state intervention through the extension of existing legislation to platform workers.